2006
DOI: 10.1002/jrs.1438
|View full text |Cite
|
Sign up to set email alerts
|

Degenerate and two‐color resonant four‐wave mixing applied to the rotational characterization of high‐lying vibrational states of formaldehyde (Ã, 1A2)

Abstract: Degenerate and two-color resonant four-wave mixing techniques (DFWM and TC-RFWM) are applied to determine rotational constants of high-lying vibrational levels in the first excited singlet stateÃ( 1 A 2 ) of formaldehyde. It has been demonstrated that the sensitivity of the spectroscopic technique is applicable to the low-density environment of a supersonic molecular beam and to predissociating transitions displaying low fluorescence quantum yield. In addition, we take advantage of the superior selectivity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…This method was used to investigate the dynamics of the radical channel decomposition of H 2 CO. Tulej et al 147 determined rotational constants of high-lying vibrational levels in the first excited singlet state of formaldehyde from DFWM measurements. 143 The technique, called 'four-photon Rayleigh-wing Spectroscopy' by the authors, was also successfully applied for the study of˛chymotrypsin protein in water 144 and for the determination of the fraction dimensionality in liquids.…”
Section: Other Nonlinear Techniquesmentioning
confidence: 99%
“…This method was used to investigate the dynamics of the radical channel decomposition of H 2 CO. Tulej et al 147 determined rotational constants of high-lying vibrational levels in the first excited singlet state of formaldehyde from DFWM measurements. 143 The technique, called 'four-photon Rayleigh-wing Spectroscopy' by the authors, was also successfully applied for the study of˛chymotrypsin protein in water 144 and for the determination of the fraction dimensionality in liquids.…”
Section: Other Nonlinear Techniquesmentioning
confidence: 99%
“…The simulation of the absorption spectrum is shown inverted by taking into account line positions and Hönl-London factors from the pgopher [70] program package and adopting the relevant rotational constants for the ground and excited state from the literature. [12] Several investigations in this laboratory [50] and by other groups [54,71 -74] have shown that for carefully controlled conditions of the experiment (i.e. collision-free environment of the molecular beam, I I sat , parallel polarization of the input beams) the DFWM signal expression is given by the relation I DFWM ∝ N 2 µ 4 , where N and µ are the number density in the lower rotational state and transition dipole moment, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…For the double-resonance experiment, one of the three incident beams (k 2 ) is replaced by a laser beam of a different frequency (PROBE beam) to establish the forward BOXCARS configuration for TC-RFWM. [42,48,50,69] The equal-frequency input beams (k 1 and k 3 ) are commonly referred to as PUMP beams.…”
Section: Introductionmentioning
confidence: 99%
“…Further details of the theoretical principles of nonlinear phenomena can be found in a number of textbooks 17,62,94 and review articles. 95,96 The list of FWM techniques for advanced optical diagnostics is quite long and includes degenerate four-wave mixing (DFWM), [97][98][99][100][101] two-color FWM (TC-FWM), [102][103][104][105] polarization spectroscopy (PS), [106][107][108][109][110][111] CARS, 96 and LIGS also known as laser-induced thermal acoustics (LITA). [112][113][114] In the following, we will focus on the developments of the two latter, CARS and LIGS, and eventually review combined applications of linear and nonlinear methods.…”
Section: 93mentioning
confidence: 99%